We Are Not Born Alone and We Do Not Die Alone: Protecting Intergenerational Solidarity and Refraining Cain-ism Through Forced Heirship - Albert Lamarca i Marquès (Oñati Socio-Legal Series)
In the current academic debate on family and succession law, the abolition or reform of forced heirship is often advocated. It is argued that this institution does not respond to the expectations and needs of today’s society. In the realm of freedom embodied by testate succession by will, the mandatory share is framed as a contradictory restriction on the individual right to decide freely. This paper contributes to the debate on the legal and social basis of forced heirship by offering a moderate defence of the institution. I argue that forced heirship actually protects individual choice while also respecting intergenerational ties. Moreover, the institution restrains competition and opportunistic behavior among siblings. It reflects the reality that we are alone in neither birth nor death and it reins in the Cain-like tendencies that threaten to tear apart families.